ALTHUSSER´S KEYS TO READ ALVARO GARCÍA LINERA´S MARXISM - Parodi, Ramiro (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2016)
Where can we find Marxism today? Answering this question raises a problem that Jacques Derrida assumed when he said: “there is more than one of them, there must be more than one of them (them meaning Marx´s ghosts)” Then, which is the Marx that Althusser invites us to read and to translate into political action? The aim of this text is to trace the guidelines of the Marx that Althusser shapes (through the concepts of political practice and theoretical practice) in Álvaro García Linera´s thought.These althusserian concepts allow us to propose Álvaro García Linera as the “heir” (Derrida, 1995) of Marxist philosophy and as a theorist of revolution today. His militant condition and his position as Bolivia´s vice-president determine his theoretical production because he does not develop this production in the middle of nothingness but writes in a very particular political situation. Thus, we can understand that García Linera addresses in his theoretical practice something that is objectively present in the historical process during which, and about which, he is writing: the liberating power of the indigenous people.We are going to focus on Linera´s re-reading of the Communist Manifesto though these althusserian concepts in order to get a deeper scope of a thought that invokes Marx at the same time that it highlights the necessity of thinking within the political situation. By doing this, we are not aiming to make conclusions about its truthfulness or falsehood; instead, we are trying to produce a political analysis of his discourse in order to research the contradictions which emerge when Marx is read through the variants that the political situation proposes and, by doing this, we are also trying to deepen the studies in communication and politics. We will also go through interviews, conferences and other texts written by the vice president of Bolivia to locate the most recent developements of his thoughts. Our aim is to start tracing a series of interlocutors with which García Linera contends and argues, in order to set the basis of a research process that will deepen the analysis of his works.